INCREASE IN THE ARRAY TELEVISION CAMERA SENSITIVITY - Shakhrukhanov, O. S. (Одеські астрономічні публікації, 2013)
A simple adder circuit for successive television frames that enables to considerably increase the sensitivity of such radiation detectors is suggested by the example of array television camera QN902K